A MEMS INERTIAL MEASUREMENT APPROACH FOR LOW-COST MONITORING OF ROLL, PITCH, AND YAW IN SEAKEEPING - Wibowo, Yuni Ari; Baswantara, Arif; Firdaus, Anas Noor; Kusdinar, Afriana; Destiana, Atik Ghina (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Abstract—Seakeeping tests are crucial for assessing the safety and dynamic performance of floating structures. However, conventional approaches often rely on costly sensors and specialized facilities such as the Maneuvering Ocean Basin (MOB), limiting broader access to motion evaluation. This study presents a low-cost measurement system for monitoring rotational ship motions (roll, pitch, and yaw) using microelectromechanical systems (MEMS) sensors, namely the MPU-6050 accelerometer and gyroscope combined with an HMC5883L magnetometer. Calibration was conducted against a high-precision reference sensor, the 3DM-GX5-25, under both static and dynamic conditions. Static calibration utilized a precision mechanical protractor to determine correction factors and linear regression models, while the dynamic validation was performed on an oscillation table to assess the sensor response under periodic motion. Calibration results indicate error levels of 2.48% for roll and 15.96% for pitch, showing good agreement with the reference sensor, while yaw measurements exhibit a relatively higher error of 88.08%, indicating limitations in measurement accuracy associated with the employed sensor configuration, particularly in readings referenced to true north. Nevertheless, these findings highlight the potential of the proposed system as a reliable and cost-effective alternative for rotational motion measurements in seakeeping studies, particularly for roll and pitch evaluation, and as a basis for further improvement in yaw measurement accuracy, thereby enabling wider accessibility to ship motion performance evaluation